2015
DOI: 10.1371/journal.pone.0115828
|View full text |Cite
|
Sign up to set email alerts
|

S100A9 Induced Inflammatory Responses Are Mediated by Distinct Damage Associated Molecular Patterns (DAMP) Receptors In Vitro and In Vivo

Abstract: Release of endogenous damage associated molecular patterns (DAMPs), including members of the S100 family, are associated with infection, cellular stress, tissue damage and cancer. The extracellular functions of this family of calcium binding proteins, particularly S100A8, S100A9 and S100A12, are being delineated. They appear to mediate their functions via receptor for advanced glycation endproducts (RAGE) or TLR4, but there remains considerable uncertainty over the relative physiological roles of these DAMPs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
89
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(108 citation statements)
references
References 61 publications
(92 reference statements)
10
89
0
1
Order By: Relevance
“…Other pathways may also be activated. S100A9-induced airway inflammation in mice for example, was reported to occur independent of both RAGE and TLR4 signaling (Chen et al 2015). Thus, the roles for the S100A8/A9-TLR4 axis in the modulation of immune responses are still not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Other pathways may also be activated. S100A9-induced airway inflammation in mice for example, was reported to occur independent of both RAGE and TLR4 signaling (Chen et al 2015). Thus, the roles for the S100A8/A9-TLR4 axis in the modulation of immune responses are still not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…S100A8 and S100A9 belong to the S100 family proteins and are constitutively expressed in monocytes and neutrophils [9][10][11]. They play as damage-associated molecular pattern (DAMP) via Toll-like receptor 4 (TLR4) and receptor for advanced glycation endproducts (RAGE), and triggers the pathogenesis of asthma, chronic obstructive pulmonary disease, colitis, rheumatoid arthritis, Alzheimer's disease, and tumor [12,13]. Our reports recently demonstrated that S100A8 and S100A9 induce cytokine secretion, which is involved in regulation of neutrophil apoptosis [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…It also belongs to the family of damage-associated molecular patterns (DAMPs). Studies have shown that S100A8 plays an important role in regulating tissue inflammation as a ligand of toll-like receptor 4 (TLR4) and/or receptor for advanced glycation end products (RAGE) (7,8). Aberrant expression of S100A8 has been found in different types of tumors including CRC (9) and the accumulation of S100A8 positive cells is always located in the invasive margin of colorectal carcinoma (10) which plays a critical role in the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%